An evaluation of the role and functioning of an appeal authority created in terms of Section 62 of the Local Government : Municipal Systems Act 32 of 2000 - Bekink, Bernard (University of Pretoria, 2014)
Dissertation (LLM)--University of Pretoria, 2013.